ANALYZING HOW MIS CAN OPTIMIZE THE DISTRIBUTION OF ENERGY IN SMART GRIDS, FOCUSING ON DATA-DRIVEN DECISION-MAKING PROCESSES - Anwar Hossain; Dorcas Oyebode; Kazi Abdullah Al Imon; Shah Md. Wasif Faisal; Rajesh Vayyala; Mohammed Alaa H. Altemimi (Spectrum of Engineering Sciences, 2025)
This paper evaluates how MIS advance the capabilities of smart grids by helping implementers make optimal decisions in areas such as energy distribution and demand improve the mechanisms for monitoring smart grids. The use of management information systems in energy distribution has changed the administration of smart grids. An integrated power network that uses advanced technologies for the efficient distribution and consumption of resources and for sustainability. MIS offers the basis for automatically and dynamically developing new energy networks. A qualitative analysis of information gathered to assess the contribution of MIS in enhancing the effectiveness of smart grids. International experiences in smart grids and related empirical evidence incorporated in forming the case studies are examined to assess their efficiency. Primary data sources include operation statistics and trends in energy use and other parameters, as well as analytical models employed by MIS frameworks. This statistical modeling and machine learning algorithms are used to run different performance analyses and make predictions in response to the different conditions of the grid. The noted results point directly at the potential for MIS in the context of optimizing energy distribution in smart grids. MIS provides real-time decision-making and control over the energy grid through competent data analytics and forecasting, thus reducing downstream energy wastage while improving the reliability of the grid. MIS is an important enabler of the shift towards sustainable energy systems by enabling optimal resource allocation and incorporating renewable resources. This research underscores the requirements to commit more in subjects of MIS technologies and the integrated public and private interaction between regulators, technologists, and energy providers to get the enhanced intelligent grid. Keywords ( management information systems, smart grids, energy distribution, data-driven decision-making, energy optimization, renewable energy integration).